Bloody nipple discharge in an infant - Cristina F. Rodrigues; Nicole Silva (Hygeia Press di Corridori Marinella, 2021)
Bloody nipple discharge (BND) is rare in the pediatric age. Mammary duct ectasia presents as its main cause. This entity can be very distressing because of its association with breast cancer in adults; however, most infancy and childhood breast lesions are benign. The diagnostic approach should be conservative, with ultrasound being the preferred method of evaluation. The usual treatment is watchful clinical observation because BND is usually self-limited with spontaneous resolution. We report the case of a previously healthy 8-month-old female infant with normal development. She presented with a right BND with 3 days of evolution; the left breast was normal. Ultrasound of the right breast revealed dilated mammary ducts. A conservative approach was chosen with follow-up in a pediatric consultation. A month later, a similar episode occurred, lasting only 1 day. Subsequently, there has been no recurrence of the nipple discharge. The patient is now 18 months old and has no residual symptoms.